Salp15, a Multifunctional Protein From Tick Saliva With Potential Pharmaceutical Effects - Wen, Shiyuan; Wang, Feng; Ji, Zhenhua; Pan, YingYi; Jian, Miaomiao; Bi, YunFeng; Zhou, Guozhong; Luo, Lisha; Chen, Taigui; Li, Lianbao; Ding, Zhe; Abi, Manzama-Esso; et al. (Frontiers in Immunology, 2020)
Ixodes ticks are the main vectors for a number of zoonotic diseases, including Lyme disease. Ticks of the Ixodes genus secrete saliva directly into a mammalian host while feeding on the host’s blood. This action serves to modulate host immunity and coagulation, thus allowing ticks to attach and feed upon their host. One of the most extensively studied components of tick saliva is Salp15. Research has shown that this protein binds specifically to CD4 molecules on the surface of T lymphocytes, interferes with TCR-mediated signaling transduction, inhibits CD4+ T cell activation and proliferation, and impedes the secretion of interleukin 2 (IL-2). Salp15 also binds specifically to dendritic cell dendritic cell-specific intercellular adhesion molecule-3-grabbing non-integrin (DC-SIGN) to up-regulate the expression of CD73 in regulatory T cells. Collectively, these findings render this salivary protein as a potential candidate for a range of therapeutic applications. Here, we discuss our current understanding of Salp15 and the mechanisms that might be used to treat disease.